Light-Chain Amyloidosis With Peripheral Neuropathy as an Initial Presentation - Qian, Min; Qin, Lan; Shen, Kaini; Guan, Hongzhi; Ren, Haitao; Zhao, Yanhuan; Guan, Yuzhou; Zhou, Daobin; Peng, Bin; Li, Jian; Chen, Lin (Frontiers in Neurology, 2021)
Objective: This study aimed to better understand the clinical, electrophysiological, pathological features and prognosis of peripheral nerve involvements in primary immunoglobulin light-chain (AL) amyloidosis. Methods: We retrospectively reviewed the clinical data of eight AL amyloidosis patients with peripheral neuropathy as the initial presentation including clinical features, histopathological findings and treatment. Results: There were seven males and one female aged from 52 to 66 years. Initial symptoms included symmetrical lower extremity numbness, lower extremity pain and carpal tunnel syndrome. Seven patients suffered from severe pain and required pain management. Six patients had predominant autonomic dysfunction. Six patients had cardiac involvement, and one patient had renal involvement. Monoclonal proteins were found in all patients, with IgA λ in one, IgG λ in two, λ alone in three, κ alone in one and IgM κ in one. Sural nerve biopsies were performed in 7 cases, all of which showed amyloid deposition in the endoneurium (in the perivascular region in some cases), in addition to moderate to severe myelinated fiber loss with axonal degeneration. Six patients were treated with combined chemotherapy. In three patients who began chemotherapy earlier (6–10 months after onset), two achieved a hematological complete response, and one achieved a partial response. three patients who had delayed chemotherapy (36 months after onset) died between 5 and 12 months after diagnosis. Conclusion: Early recognition of AL amyloidosis with peripheral neuropathy as the initial symptom is very important. Nerve biopsy can help to make the diagnosis. Early diagnosis and chemotherapy are critical to achieve better outcomes.